2011
DOI: 10.5152/akd.2011.159
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-modified albumin and total antioxidant status in patients with slow coronary flow: a pilot observational study

Abstract: ÖZETAmaç: Yavaş koroner akım (YKA) önemli darlık olmaksızın epikardiyal koroner arterlerin geç opasifiye olmasıdır. Yavaş koroner akım oluşumundaki temel mekanizma koroner ateroskleroza benzer ve serbest radikal oluşumu patolojiden sorumlu olabilir. Biz bu çalışmada, normal koroner arterli hastalarla, daralma olmaksızın YKA bulunan hastalar arasında iskemi-modifiye albümin (İMA) seviyeleri ve total antioksidan durum (TAD) açısından farklılık olup olmadığını araştırdık. Yöntemler: Koroner anjiyografi sırasında … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Importantly, appendicitis is associated with changes in serum albumin 5 . Given prior evidence indicating that serum albumin changes in acute appendicitis 5 6 and that albumin levels can affect the estimation of IMA 4 , 7 , it is extremely important to provide serum albumin levels and IMA values that are corrected for albumin interference, as previously reported 7 . This evidence could strongly suggest the need to evaluate IMA as an oxidative stress marker in combination with albumin in individuals with acute appendicitis.…”
mentioning
confidence: 97%
“…Importantly, appendicitis is associated with changes in serum albumin 5 . Given prior evidence indicating that serum albumin changes in acute appendicitis 5 6 and that albumin levels can affect the estimation of IMA 4 , 7 , it is extremely important to provide serum albumin levels and IMA values that are corrected for albumin interference, as previously reported 7 . This evidence could strongly suggest the need to evaluate IMA as an oxidative stress marker in combination with albumin in individuals with acute appendicitis.…”
mentioning
confidence: 97%
“…However, this is the first report demonstrating both IMA and AAIMA in patients with diabetic retinopathy. It is important to study IMA result adjusted for albumin levels, because of dependence of IMA values on serum albumin concentrations (Koc et al, 2011 Our finding of an increase in IMA values in diabetic retinopathy indicates structural/ functional/chemical modification of HSA, resulting in an increased IMA formation. Increased IMA formation is regarded as a marker of ischemia and oxidative stress.…”
Section: Discussionmentioning
confidence: 74%
“…It has also been reported that a 1% change in albumin concentration can produce a 2% opposite change in IMA values (Zapico-Muñiz et al, 2004). Given the previous evidence of decreased serum albumin levels in diabetic disease (Yukl et al, 2003), and the interference of albumin level with the IMA estimation (Koc et al, 2011;Zapico-Muñiz et al, 2004), it is important to provide IMA values corrected for albumin interference. In the present study, IMA results were corrected for albumin interference and found that, even after correcting for albumin changes, the AAIMA values were significantly higher in the patient group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations